1987
DOI: 10.1038/clpt.1987.45
|View full text |Cite
|
Sign up to set email alerts
|

The effect of methotrexate on the bioavailability of oral 6-mercaptopurine

Abstract: Fourteen children (aged 3 to 14 years) with average-risk acute lymphoblastic leukemia were studied after an oral dose of 6-mercaptopurine (6-MP) (75 mg/m2) administered alone and, on the next day, concurrently with oral methotrexate (20 mg/m2). When 6-MP was administered alone, both the peak plasma concentration (15 to 150 ng X ml-1) and the AUC (36 to 340 ng X ml-1 X hr) were highly variable. Concurrent methotrexate resulted in a 31% increase in the AUC (P less than 0.01) and a 26% increase in peak plasma lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 0 publications
2
41
0
Order By: Relevance
“…28 Finally, low-dose MTX as well as HDM can inhibit xanthine oxidase and enhance the bioavailability of 6MP. 14,29 These interactions between 6MP and MTX were indicated by clinical studies more than 30 years ago when 6MP/MTX combination maintenance therapy for childhood ALL was shown to be superior to monotherapy with either MTX or 6MP. 30,31 In recent years both in vitro and in vivo studies have supported that the interaction between 6MP and MTX is of clinical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Finally, low-dose MTX as well as HDM can inhibit xanthine oxidase and enhance the bioavailability of 6MP. 14,29 These interactions between 6MP and MTX were indicated by clinical studies more than 30 years ago when 6MP/MTX combination maintenance therapy for childhood ALL was shown to be superior to monotherapy with either MTX or 6MP. 30,31 In recent years both in vitro and in vivo studies have supported that the interaction between 6MP and MTX is of clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…10 This myelosuppression may lead to treatment interruptions and a reduction of the dose intensity, which can affect the cure rate. [11][12][13] MTX may increase the bioavailability of 6MP, 14 and in addition, through inhibition of de novo purine synthesis, enhance the availability of 6TGN and its incorporation into DNA. 15 We speculated that this drug interaction could in part be responsible for the bone marrow toxicity which follows HDM given during 6MP/MTX maintenance therapy.…”
Section: Introductionmentioning
confidence: 99%
“…2 MTX may increase the bioavailability of 6MP through inhibition of xanthine oxidase, which catabolizes 6MP. 3 In addition, several studies of cytotoxicity have indicated that MTX and 6MP act synergistically. [4][5][6][7][8] In hemopoietic cells, 6MP is anabolized to 6-thioguanine nucleotides (6TGNs), which are the most important mediators of the cytotoxic effect of 6MP through incorporation into DNA.…”
Section: Introductionmentioning
confidence: 99%
“…9 Erythrocytic accumulation of 6TGN correlate with the degree of myelotoxicity and remission duration in childhood ALL. 3,10,11 Another important metabolic pathway of 6MP is the methylation of 6MP and some of its metabolites by thiopurine methyltransferase (TPMT). Methylated products of 6MP as well as MTX polyglutamates inhibit purine de novo synthesis and, thus, may enhance the incorporation of 6TGN into DNA.…”
Section: Introductionmentioning
confidence: 99%
“…MTX-induced hepatotoxicity, whether or not due to increased intestinal absorption or reduced clearance, could therefore impair 6MP breakdown, leading to treatment intensification. Along this line it has been demonstrated that 6MP plasma peak-concentration and AUC are increased with concurrent administration of MTX and 6MP, compared to 6MP given alone (Balis et al, 1987).…”
Section: Discussionmentioning
confidence: 56%